An absorbable hemostatic composite material for anti-inflammatory and healing promotion of acute bleeding sites and preparation method thereof
By combining oxidized bacterial cellulose with natural anti-inflammatory compounds or metal ions containing phenolic hydroxyl groups, composite materials with antibacterial, procoagulant and absorbable properties were prepared, which solved the problems of weak antibacterial properties, low histocompatibility and slow hemostasis of existing oxidized bacterial cellulose hemostasis materials, and achieved rapid and effective acute hemostasis and in vivo hemostatic hemostasis.
Patent Information
- Application Number
- CN202310262011.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-17
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2043-03-17
AI Technical Summary
Existing oxidized bacterial cellulose hemostatic materials have weak antibacterial properties, low histocompatibility and slow hemostatic speed.
By preparing oxidized bacterial cellulose with bacterial cellulose as substrate, and compounding it with natural anti-inflammatory compounds or metal ions containing phenolic hydroxyl groups, and by hydrogen bond adsorption self-assembly reaction or electrostatic adsorption self-assembly reaction, composite materials with antibacterial, procoagulant and absorbable properties are prepared.
It improves the antibacterial properties, procoagulant ability and biodegradable properties of the material, achieves rapid and effective acute hemostasis, and promotes healing in the body, reducing inflammatory response.
Smart Images

Figure CN116370695B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of biomedical composite materials, and particularly relates to an absorbable hemostatic composite material for anti-inflammation and healing promotion of acute bleeding sites and a preparation method thereof. Background Art
[0002] The characteristics of ideal hemostatic materials should be good cytocompatibility, short treatment time, no negative impact on the healing process of tissues, minimal inflammatory response, and no increased likelihood of infection. They should also be non-toxic, non-irritating, non-antigenic, soft, breathable, and permeable. Various materials, including collagen, alginate, chitosan, graphene, cellulose, and gelatin, have been shown to be effective in controlling bleeding. However, these products have not been widely used in clinical practice due to the scarcity of raw materials, high preparation costs, and potential infection risks.
[0003] As an excellent natural biomaterial, bacterial cellulose has great prospects in medical applications due to its advantages such as nano-network structure similar to extracellular matrix and good biocompatibility. However, bacterial cellulose cannot be degraded in the body. During the degradation process, although the acidic carboxyl groups of oxidized cellulose-based gauze can inhibit the growth of bacteria, it can also cause aseptic inflammation. Tannic acid has been shown to be an effective anti-inflammatory agent, and its antioxidant properties can prevent oxidative stress in tissues, which is one of the main causes of inflammation. The anti-inflammatory effect of tannic acid can be used to reduce the disadvantages of local acidity of oxidized cellulose and promote wound healing, providing a new development direction for hemostatic materials.
[0004] At present, in some public or authorized invention patents, natural / synthetic polymer materials or inorganic materials have been used to modify oxidized regenerated cellulose to improve its antibacterial and hemostatic properties. Such as coagulation factor (CN110339391A), collagen (CN105079886A), alginate (CN104013991A) and carbon nanotubes (CN105056284A). Although the above composite hemostatic materials have improved the performance of oxidized regenerated cellulose to a certain extent, the improvement effect is poor, and can only improve its partial performance, and will have a negative impact on the bioabsorbable properties of the material. With the increasing requirements of the medical community in various countries for the hemostatic performance of hemostatic materials, it is imperative to develop materials with better hemostatic effects. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide an absorbable hemostatic composite material for anti-inflammatory and healing of acute bleeding sites and a preparation method thereof, which solves the problems of weak antibacterial performance, low tissue compatibility and slow hemostasis of oxidized bacterial cellulose.
[0006] The present invention provides an absorbable hemostatic composite material for anti-inflammatory and promoting healing of acute bleeding sites. The oxidized bacterial cellulose is prepared by oxidation using bacterial cellulose as a substrate, and then compounded with a natural anti-inflammatory compound containing phenolic hydroxyl groups; or the oxidized bacterial cellulose is prepared by using bacterial cellulose as a substrate, and then electrostatically adsorbed and self-assembled with metal ions, and the natural anti-inflammatory compound containing phenolic hydroxyl groups is complexed and loaded to obtain the composite material.
[0007] The oxidized bacterial cellulose is obtained by taking bacterial cellulose as a substrate, oxidizing it and rinsing it with deionized water until it becomes neutral.
[0008] The natural anti-inflammatory compound containing phenolic hydroxyl group is one or more of tannic acid, catechin and anthocyanin.
[0009] The metal ions are one or more of magnesium ions, calcium ions, iron ions and zinc ions.
[0010] The present invention also provides a method for preparing an absorbable hemostatic composite material for anti-inflammatory and healing-promoting treatment of acute bleeding sites, comprising the following steps:
[0011] (1) Using bacterial cellulose as a substrate, preparing an oxidized bacterial cellulose suspension;
[0012] (2) dripping the aqueous solution of the natural anti-inflammatory compound containing phenolic hydroxyl group into the oxidized bacterial cellulose suspension drop by drop to perform a mixing and assembly reaction, then centrifugally rinsing, redispersing evenly, and freeze-drying to obtain an absorbable hemostatic composite material;
[0013] Alternatively, a metal ion solution is dripped into an oxidized bacterial cellulose suspension for mixed adsorption, and then an aqueous solution of a natural anti-inflammatory compound containing phenolic hydroxyl groups is dripped dropwise into the oxidized bacterial cellulose suspension for metal ion complexation reaction, followed by centrifugal rinsing, redispersing evenly, and freeze-drying to obtain an absorbable hemostatic composite material.
[0014] The preparation steps of the oxidized bacterial cellulose suspension in step (1) are as follows: the bacterial cellulose membrane is dispersed by a homogenizer, oxidized by a TEMPO / NaBr / NaClO mixed oxidation system at room temperature, and obtained after centrifugal washing and dialyzation.
[0015] The solid content of the oxidized bacterial cellulose suspension in step (1) is 1-10%.
[0016] The aqueous solution of natural anti-inflammatory compounds containing phenolic hydroxyl groups in step (2) is one or more of a tannic acid aqueous solution, a catechin aqueous solution, and anthocyanin aqueous solution with a concentration of 1-5 wt%.
[0017] The metal ion solution in step (2) is one or more of a magnesium sulfate aqueous solution, a calcium chloride aqueous solution, a ferric chloride aqueous solution, and a zinc chloride aqueous solution with a concentration of 0.1-1 mg / mL.
[0018] The mass ratio of the natural anti-inflammatory compound containing phenolic hydroxyl groups to the oxidized bacterial cellulose in the step (2) is 1:1-1:5; the mass ratio of the metal ions to the oxidized bacterial cellulose is 1:10-1:20.
[0019] The mixing and assembly reaction time in step (2) is 1-60 minutes.
[0020] The adsorption time in step (2) is 0.5-5 hours.
[0021] The complexation reaction time in step (2) is 1-60 minutes.
[0022] The present invention uses bacterial nanocellulose as a substrate to prepare oxidized bacterial cellulose (OBC), and utilizes its high purity and large specific surface area characteristics to accelerate the coagulation process. At the same time, the abundant hydroxyl groups of OBC and natural anti-inflammatory compounds are used to carry out hydrogen bond adsorption self-assembly reaction for compounding, and metal ions can also be introduced therein to prepare an absorbable composite material with acute hemostasis, antibacterial and healing-promoting functions.
[0023] Beneficial Effects
[0024] (1) The present invention uses bacterial cellulose as a substrate to prepare oxidized bacterial cellulose, which has a higher hydroxyl content, nanoscale fibers, a larger specific surface area, a lower degree of polymerization, a better hemostatic effect, better biodegradability, and is more easily absorbed by the human body.
[0025] (2) The present invention utilizes oxidized bacterial cellulose and the phenolic hydroxyl groups of natural anti-inflammatory compounds for hydrogen bond adsorption self-assembly preparation without the use of additional cross-linking agents; at the same time, the addition of natural anti-inflammatory compounds improves the procoagulant and antibacterial properties of the material.
[0026] (3) The present invention utilizes the large specific surface area of oxidized bacterial cellulose to fully adsorb metal ions and then undergo a complex self-assembly reaction with phenolic hydroxyl compound molecules. The resulting material has the properties of acute hemostasis, antibacterial, healing promotion and absorbability.
[0027] (4) The raw materials of the present invention are all green and environmentally friendly biological materials, do not contain chemicals harmful to the human body, can be prepared into various shapes according to actual conditions and characteristics, are safe and environmentally friendly, and can be rapidly degraded in the environment after being discarded. They can be used as a functional material with good performance and green and environmental protection.
[0028] (5) The present invention uses a metal phenol network structure formed by metal ions and natural anti-inflammatory compounds containing phenolic hydroxyl groups to uniformly deposit the natural anti-inflammatory compounds on the surface of nanocellulose. Compared with the composite method of polycationic electrolytes, the obtained material is more uniform and has a high composite efficiency. At the same time, it can also carry out sustained release of antioxidant and anti-inflammatory compounds, so that the material has antioxidant effects for a longer period of time.
[0029] (6) The present invention directly enhances the antibacterial, hemostatic and healing abilities of oxidized bacterial cellulose materials through natural anti-inflammatory compounds containing phenolic hydroxyl groups. As natural compounds, they have good biocompatibility and availability. At the same time, they can avoid the hazards caused by the use of polycations, such as the potential hazards or immune responses such as "mad cow disease" that may be caused by terrestrial animal-derived gelatin and collagen, and the high cytotoxicity caused by chitosan and polylysine.
[0030] (7) The preparation method of the present invention is simple and easy to implement, has uniform and efficient compounding, does not use a cross-linking agent, will not damage the original structure of the synthetic substance, can be industrially produced, and has good market application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 Schematic diagram of the process of preparing materials for the examples.
[0032] Figure 2 The material product diagram prepared in the example; 1-5 are OBC, OBC / TA, OBC / Ca 2+ / TA、OBC / Fe 3+ / TA and OBC / Mg 2+ / TA.
[0033] Figure 3 It is a scanning electron microscope image of the material products prepared in Examples 1-5.
[0034] Figure 4 The red blood cell adhesion results of the material products prepared in Examples 1-5.
[0035] Figure 5 In vitro whole blood coagulation curve (A) and hemolysis rate test results (B) of the material products prepared in Examples 1-5.
[0036] Figure 6 These are the in vivo hemostasis test results of the material products prepared in Examples 1-5.
[0037] Figure 7 The blood absorption amount (A) and hemostasis time (B) recorded in the in vivo hemostasis experiment of the material products prepared in Examples 1-5.
[0038] Figure 8These are the in vivo degradability and tissue compatibility evaluation results of the material products prepared in Examples 1-5.
[0039] Fig. 9 The difference in phenolic hydroxyl content of the material products prepared in Examples 6-9.
[0040] Fig.10 In vitro whole blood coagulation curves of the material products prepared in Examples 1 and 6-9. DETAILED DESCRIPTION
[0041] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0042] Example 1
[0043] (1) Acetobacter xylinum was used as the bacterial species, and after being cultured in a liquid culture medium at a constant temperature for 10 days, a bacterial cellulose membrane was taken out and placed in a sodium hydroxide solution. After being treated at 80°C for 2 hours, the membrane was taken out and rinsed with deionized water until neutral to obtain a bacterial cellulose membrane.
[0044] (2) Weigh 300 g of the purified bacterial cellulose membrane, cut it into pieces, and then disperse it in a high-speed homogenizer to obtain a bacterial cellulose suspension.
[0045] (3) 500 mL of the bacterial cellulose suspension (solid content of 5 g / L) obtained in step (2) was oxidized at room temperature using a TEMPO / NaBr / NaClO mixed oxidation system, with a TEMPO dosage of 0.1 mmol / g and a NaBr dosage of 1 mmol / g. 20 mL of a 10% NaClO solution was added to start the reaction. The pH of the reaction system was maintained at 10±0.5 by dropwise addition of a 0.5 M NaOH solution. When no more NaOH solution was consumed, ethanol was added to terminate the reaction. The obtained oxidation product was centrifuged, rinsed, and sterilized under high pressure and then stored at 4°C. The hydroxyl content of the TEMPO-oxidized bacterial cellulose suspension was measured by conductivity titration to be 23%.
[0046] (4) freeze-drying the oxidized bacterial cellulose suspension obtained in step (3) to obtain an oxidized bacterial cellulose hemostatic material.
[0047] Example 2
[0048] (1) Acetobacter xylinum was used as the bacterial species, and after being cultured in a liquid culture medium at a constant temperature for 10 days, a bacterial cellulose membrane was taken out and placed in a sodium hydroxide solution. After being treated at 80°C for 2 hours, the membrane was taken out and rinsed with deionized water until neutral to obtain a bacterial cellulose membrane.
[0049] (2) Weigh 300 g of the purified bacterial cellulose membrane, cut it into pieces, and then disperse it in a high-speed homogenizer to obtain a bacterial cellulose suspension.
[0050] (3) 500 mL of the bacterial cellulose suspension (solid content of 5 g / L) obtained in step (2) was oxidized at room temperature using a TEMPO / NaBr / NaClO mixed oxidation system, with a TEMPO dosage of 0.1 mmol / g and a NaBr dosage of 1 mmol / g. 20 mL of a 10% NaClO solution was added to start the reaction. The pH of the reaction system was maintained at 10±0.5 by dropwise addition of a 0.5 M NaOH solution. When no more NaOH solution was consumed, ethanol was added to terminate the reaction. The obtained oxidation product was centrifuged, rinsed, and sterilized under high pressure and then stored at 4°C. The hydroxyl content of the TEMPO-oxidized bacterial cellulose suspension was measured by conductivity titration to be 23%.
[0051] (4) Weigh 1 g of tannic acid and fully dissolve it in 100 mL of deionized water to form a tannic acid aqueous solution with a final concentration of 10 mg / mL.
[0052] (5) Take 10 mL of the tannic acid aqueous solution prepared in step (4) and add it dropwise to 20 mL of the oxidized bacterial cellulose suspension prepared in step (3). After reacting for 30 minutes, the product is repeatedly centrifuged and rinsed, and finally freeze-dried to obtain an oxidized bacterial cellulose / tannic acid composite hemostatic material.
[0053] Example 3
[0054] (1) Acetobacter xylinum was used as the bacterial species, and after being cultured in a liquid culture medium at a constant temperature for 10 days, a bacterial cellulose membrane was taken out and placed in a sodium hydroxide solution. After being treated at 80°C for 2 hours, the membrane was taken out and rinsed with deionized water until neutral to obtain a bacterial cellulose membrane.
[0055] (2) Weigh 300 g of the purified bacterial cellulose membrane, cut it into pieces, and then disperse it in a high-speed homogenizer to obtain a bacterial cellulose suspension.
[0056] (3) 500 mL of the bacterial cellulose suspension (solid content of 5 g / L) obtained in step (2) was oxidized at room temperature using a TEMPO / NaBr / NaClO mixed oxidation system, with a TEMPO dosage of 0.1 mmol / g and a NaBr dosage of 1 mmol / g. 20 mL of a 10% NaClO solution was added to start the reaction. The pH of the reaction system was maintained at 10±0.5 by dropwise addition of a 0.5 M NaOH solution. When no more NaOH solution was consumed, ethanol was added to terminate the reaction. The obtained oxidation product was centrifuged, rinsed, and sterilized under high pressure and then stored at 4°C. The hydroxyl content of the TEMPO-oxidized bacterial cellulose suspension was measured by conductivity titration to be 23%.
[0057] (4) Weigh 0.1 g of anhydrous calcium chloride and fully dissolve it in 100 mL of deionized water to form a calcium chloride solution with a final concentration of 1 mg / mL.
[0058] (5) Take 1 mL of the calcium chloride solution prepared in step (4) and add it to 20 mL of the oxidized bacterial cellulose suspension prepared in step (3), and stir it thoroughly for adsorption for 1 hour to obtain an oxidized bacterial cellulose suspension adsorbed with calcium ions.
[0059] (6) Weigh 1 g of tannic acid and fully dissolve it in 100 mL of deionized water to form a tannic acid aqueous solution with a final concentration of 10 mg / mL.
[0060] (7) Take 10 mL of the tannic acid aqueous solution prepared in step (6) and add it dropwise to 21 mL of the oxidized bacterial cellulose-calcium ion suspension prepared in step (5). After reacting for 30 minutes, the product is repeatedly centrifuged and rinsed, and finally freeze-dried to obtain an oxidized bacterial cellulose / calcium ion / tannic acid composite hemostatic material.
[0061] Example 4
[0062] (1) Acetobacter xylinum was used as the bacterial species, and after being cultured in a liquid culture medium at a constant temperature for 10 days, a bacterial cellulose membrane was taken out and placed in a sodium hydroxide solution. After being treated at 80°C for 2 hours, the membrane was taken out and rinsed with deionized water until neutral to obtain a bacterial cellulose membrane.
[0063] (2) Weigh 300 g of the purified bacterial cellulose membrane, cut it into pieces, and then disperse it in a high-speed homogenizer to obtain a bacterial cellulose suspension.
[0064] (3) 500 mL of the bacterial cellulose suspension (solid content of 5 g / L) obtained in step (2) was oxidized at room temperature using a TEMPO / NaBr / NaClO mixed oxidation system, with a TEMPO dosage of 0.1 mmol / g and a NaBr dosage of 1 mmol / g. 20 mL of a 10% NaClO solution was added to start the reaction. The pH of the reaction system was maintained at 10±0.5 by dropwise addition of a 0.5 M NaOH solution. When no more NaOH solution was consumed, ethanol was added to terminate the reaction. The obtained oxidation product was centrifuged, rinsed, and sterilized under high pressure and then stored at 4°C. The hydroxyl content of the TEMPO-oxidized bacterial cellulose suspension was measured by conductivity titration to be 23%.
[0065] (4) Weigh 0.1 g of ferric chloride and fully dissolve it in 100 mL of deionized water to form a ferric chloride solution with a final concentration of 1 mg / mL.
[0066] (5) Take 1 mL of the ferric chloride solution prepared in step (4) and add it to 20 mL of the oxidized bacterial cellulose suspension prepared in step (3), and stir it thoroughly for adsorption for 1 hour to obtain an oxidized bacterial cellulose suspension adsorbed with iron ions.
[0067] (6) Weigh 1 g of tannic acid and fully dissolve it in 100 mL of deionized water to form a tannic acid aqueous solution with a final concentration of 10 mg / mL.
[0068] (7) Take 10 mL of the tannic acid aqueous solution prepared in step (6) and add it dropwise to 21 mL of the oxidized bacterial cellulose-iron ion suspension prepared in step (5). After reacting for 30 minutes, the product is repeatedly centrifuged and rinsed, and finally freeze-dried to obtain an oxidized bacterial cellulose / iron ion / tannic acid composite hemostatic material.
[0069] Example 5
[0070] (1) Acetobacter xylinum was used as the bacterial species, and after being cultured in a liquid culture medium at a constant temperature for 10 days, a bacterial cellulose membrane was taken out and placed in a sodium hydroxide solution. After being treated at 80°C for 2 hours, the membrane was taken out and rinsed with deionized water until neutral to obtain a bacterial cellulose membrane.
[0071] (2) Weigh 300 g of the purified bacterial cellulose membrane, cut it into pieces, and then disperse it in a high-speed homogenizer to obtain a bacterial cellulose suspension.
[0072] (3) 500 mL of the bacterial cellulose suspension (solid content of 5 g / L) obtained in step (2) was oxidized at room temperature using a TEMPO / NaBr / NaClO mixed oxidation system, with a TEMPO dosage of 0.1 mmol / g and a NaBr dosage of 1 mmol / g. 20 mL of a 10% NaClO solution was added to start the reaction. The pH of the reaction system was maintained at 10±0.5 by dropwise addition of a 0.5 M NaOH solution. When no more NaOH solution was consumed, ethanol was added to terminate the reaction. The obtained oxidation product was centrifuged, rinsed, and sterilized under high pressure and then stored at 4°C. The hydroxyl content of the TEMPO-oxidized bacterial cellulose suspension was measured by conductivity titration to be 23%.
[0073] (4) Weigh 0.1 g of magnesium chloride and fully dissolve it in 100 mL of deionized water to form a magnesium chloride solution with a final concentration of 1 mg / mL.
[0074] (5) Take 1 mL of the magnesium chloride solution prepared in step (4) and add it to 20 mL of the oxidized bacterial cellulose suspension prepared in step (3), and stir and adsorb for 1 hour to obtain an oxidized bacterial cellulose suspension adsorbed with magnesium ions.
[0075] (6) Weigh 1 g of tannic acid and fully dissolve it in 100 mL of deionized water to form a tannic acid aqueous solution with a final concentration of 10 mg / mL.
[0076] (7) Take 10 mL of the tannic acid aqueous solution prepared in step (6) and add it dropwise to 21 mL of the oxidized bacterial cellulose-magnesium ion suspension prepared in step (5). After reacting for 30 minutes, the product is repeatedly centrifuged and rinsed, and finally freeze-dried to obtain an oxidized bacterial cellulose / magnesium ion / tannic acid composite hemostatic material.
[0077] Example 6
[0078] (1) Acetobacter xylinum was used as the bacterial species, and after being cultured in a liquid culture medium at a constant temperature for 10 days, a bacterial cellulose membrane was taken out and placed in a sodium hydroxide solution. After being treated at 80°C for 2 hours, the membrane was taken out and rinsed with deionized water until neutral to obtain a bacterial cellulose membrane.
[0079] (2) Weigh 300 g of the purified bacterial cellulose membrane, cut it into pieces, and then disperse it in a high-speed homogenizer to obtain a bacterial cellulose suspension.
[0080] (3) 500 mL of the bacterial cellulose suspension (solid content of 5 g / L) obtained in step (2) was oxidized at room temperature using a TEMPO / NaBr / NaClO mixed oxidation system, with a TEMPO dosage of 0.1 mmol / g and a NaBr dosage of 1 mmol / g. 20 mL of a 10% NaClO solution was added to start the reaction. The pH of the reaction system was maintained at 10±0.5 by dropwise addition of a 0.5 M NaOH solution. When no more NaOH solution was consumed, ethanol was added to terminate the reaction. The obtained oxidation product was centrifuged, rinsed, and sterilized under high pressure and then stored at 4°C. The hydroxyl content of the TEMPO-oxidized bacterial cellulose suspension was measured by conductivity titration to be 23%.
[0081] (4) Weigh 0.5 g of catechins and fully dissolve them in 100 mL of deionized water to form a catechin aqueous solution with a final concentration of 5 mg / mL.
[0082] (5) 10 mL of the catechin aqueous solution prepared in step (4) was added dropwise into 20 mL of the oxidized bacterial cellulose suspension prepared in step (3). After reacting for 30 minutes, the product was repeatedly centrifuged and rinsed, and finally freeze-dried to obtain an oxidized bacterial cellulose / catechin composite hemostatic material.
[0083] Example 7
[0084] (1) Acetobacter xylinum was used as the bacterial species, and after being cultured in a liquid culture medium at a constant temperature for 10 days, a bacterial cellulose membrane was taken out and placed in a sodium hydroxide solution. After being treated at 80°C for 2 hours, the membrane was taken out and rinsed with deionized water until neutral to obtain a bacterial cellulose membrane.
[0085] (2) Weigh 300 g of the purified bacterial cellulose membrane, cut it into pieces, and then disperse it in a high-speed homogenizer to obtain a bacterial cellulose suspension.
[0086] (3) 500 mL of the bacterial cellulose suspension (solid content of 5 g / L) obtained in step (2) was oxidized at room temperature using a TEMPO / NaBr / NaClO mixed oxidation system, with a TEMPO dosage of 0.1 mmol / g and a NaBr dosage of 1 mmol / g. 20 mL of a 10% NaClO solution was added to start the reaction. The pH of the reaction system was maintained at 10±0.5 by dropwise addition of a 0.5 M NaOH solution. When no more NaOH solution was consumed, ethanol was added to terminate the reaction. The obtained oxidation product was centrifuged, rinsed, and sterilized under high pressure and then stored at 4°C. The hydroxyl content of the TEMPO-oxidized bacterial cellulose suspension was measured by conductivity titration to be 23%.
[0087] (4) Weigh 0.1 g of ferric chloride and fully dissolve it in 100 mL of deionized water to form a ferric chloride solution with a final concentration of 1 mg / mL.
[0088] (5) Take 1 mL of the ferric chloride solution prepared in step (4) and add it to 20 mL of the oxidized bacterial cellulose suspension prepared in step (3), and stir it thoroughly for adsorption for 1 hour to obtain an oxidized bacterial cellulose suspension adsorbed with iron ions.
[0089] (6) Weigh 0.5 g of catechins and fully dissolve them in 100 mL of deionized water to form a tannic acid aqueous solution with a final concentration of 5 mg / mL.
[0090] (7) 10 mL of the catechin aqueous solution prepared in step (6) was added dropwise into 21 mL of the oxidized bacterial cellulose-iron ion suspension prepared in step (5). After reacting for 30 minutes, the product was repeatedly centrifuged and rinsed, and finally freeze-dried to obtain an oxidized bacterial cellulose / iron ion / catechin composite hemostatic material.
[0091] Example 8
[0092] (1) Acetobacter xylinum was used as the bacterial species, and after being cultured in a liquid culture medium at a constant temperature for 10 days, a bacterial cellulose membrane was taken out and placed in a sodium hydroxide solution. After being treated at 80°C for 2 hours, the membrane was taken out and rinsed with deionized water until neutral to obtain a bacterial cellulose membrane.
[0093] (2) Weigh 300 g of the purified bacterial cellulose membrane, cut it into pieces, and then disperse it in a high-speed homogenizer to obtain a bacterial cellulose suspension.
[0094] (3) 500 mL of the bacterial cellulose suspension (solid content of 5 g / L) obtained in step (2) was oxidized at room temperature using a TEMPO / NaBr / NaClO mixed oxidation system, with a TEMPO dosage of 0.1 mmol / g and a NaBr dosage of 1 mmol / g. 20 mL of a 10% NaClO solution was added to start the reaction. The pH of the reaction system was maintained at 10±0.5 by dropwise addition of a 0.5 M NaOH solution. When no more NaOH solution was consumed, ethanol was added to terminate the reaction. The obtained oxidation product was centrifuged, rinsed, and sterilized under high pressure and then stored at 4°C. The hydroxyl content of the TEMPO-oxidized bacterial cellulose suspension was measured by conductivity titration to be 23%.
[0095] (4) Weigh 1 g of anthocyanin and fully dissolve it in 100 mL of deionized water to form an anthocyanin aqueous solution with a final concentration of 10 mg / mL.
[0096] (5) Take 10 mL of the anthocyanin aqueous solution prepared in step (4) and add it dropwise to 20 mL of the oxidized bacterial cellulose suspension prepared in step (3). After reacting for 30 minutes, the product is repeatedly centrifuged and rinsed, and finally freeze-dried to obtain an oxidized bacterial cellulose / anthocyanin composite hemostatic material.
[0097] Example 9
[0098] (1) Acetobacter xylinum was used as the bacterial species, and after being cultured in a liquid culture medium at a constant temperature for 10 days, a bacterial cellulose membrane was taken out and placed in a sodium hydroxide solution. After being treated at 80°C for 2 hours, the membrane was taken out and rinsed with deionized water until neutral to obtain a bacterial cellulose membrane.
[0099] (2) Weigh 300 g of the purified bacterial cellulose membrane, cut it into pieces, and then disperse it in a high-speed homogenizer to obtain a bacterial cellulose suspension.
[0100] (3) 500 mL of the bacterial cellulose suspension (solid content of 5 g / L) obtained in step (2) was oxidized at room temperature using a TEMPO / NaBr / NaClO mixed oxidation system, with a TEMPO dosage of 0.1 mmol / g and a NaBr dosage of 1 mmol / g. 20 mL of a 10% NaClO solution was added to start the reaction. The pH of the reaction system was maintained at 10±0.5 by dropwise addition of a 0.5 M NaOH solution. When no more NaOH solution was consumed, ethanol was added to terminate the reaction. The obtained oxidation product was centrifuged, rinsed, and sterilized under high pressure and then stored at 4°C. The hydroxyl content of the TEMPO-oxidized bacterial cellulose suspension was measured by conductivity titration to be 23%.
[0101] (4) Weigh 0.1 g of ferric chloride and fully dissolve it in 100 mL of deionized water to form a ferric chloride solution with a final concentration of 1 mg / mL.
[0102] (5) Take 1 mL of the ferric chloride solution prepared in step (4) and add it to 20 mL of the oxidized bacterial cellulose suspension prepared in step (3), and stir it thoroughly for adsorption for 1 hour to obtain an oxidized bacterial cellulose suspension adsorbed with iron ions.
[0103] (6) Weigh 1 g of anthocyanin and fully dissolve it in 100 mL of deionized water to form an anthocyanin aqueous solution with a final concentration of 10 mg / mL.
[0104] (7) Take 10 mL of the anthocyanin aqueous solution prepared in step (6) and add it dropwise to 21 mL of the oxidized bacterial cellulose-iron ion suspension prepared in step (5). After reacting for 30 minutes, the product is repeatedly centrifuged and rinsed, and finally freeze-dried to obtain an oxidized bacterial cellulose / iron ion / anthocyanin composite hemostatic material.
[0105] Table 1 Antibacterial test results of the materials prepared in Examples 1-9 against Escherichia coli, Staphylococcus aureus and Candida albicans
[0106]
[0107]
[0108] Note: Sterile gauze is the control group, and the test method is based on ISO-20743-2007.
[0109] As shown in Table 1, OBC has a certain antibacterial property, while the materials compounded with tannic acid (OBC / TA, OBC / Ca 2+ / TA、OBC / Fe 3+ / TA、OBC / Mg 2+ / TA)'s antibacterial property is significantly improved. The introduction of catechins and anthocyanins can also enhance the antibacterial ability of OBC. The excellent antibacterial property makes these materials have the potential for clinical application.
[0110] Depend on Figure 3 It can be seen that the prepared sponge samples all have uniformly distributed macroporous structures, and OBC is built by nanofibers. 2+ / TA、OBC / Fe 3+ / TA and OBC / Mg 2+ The surface of / TA is also smooth, and no natural anti-inflammatory compound-metal ion complex containing phenolic hydroxyl groups appears. This proves that the process can effectively and evenly compound anti-inflammatory compound molecules on the surface of nanocellulose.
[0111] Depend on Figure 4 It can be proved that OBC is beneficial to the adhesion of red blood cells, and tannic acid can promote this process. 2+ / TA and OBC / Fe 3+ The most red blood cells adhered to TA.
[0112] Figure 5 It is the result of in vitro hemostasis test and hemolysis rate. Figure 5 A is a whole blood coagulation test, which can reflect the procoagulant ability of the material and can show OBC / TA, OBC / Ca 2+ / TA、OBC / Fe 3+ / TA、OBC / Mg 2+ / TA has better procoagulant ability than OBC, among which OBC / Ca 2+ / TA and OBC / Fe 3+ / TA has the greatest procoagulant ability. Figure 5 B proves that the prepared OBC / TA and OBC / Ca 2+ / TA、OBC / Fe 3+ / TA and OBC / Mg 2+ The hemolysis rate of / TA materials is less than 3%, meeting the national standard requirement of <5%, and has good blood compatibility.
[0113] Depend on Figure 6 It can be seen that OBC / Fe3+ / TA material has the best blood concentration ability. It can be seen that compared with OBC and composite materials containing other metal ions, OBC / Fe 3+ / TA sponge structure is the most completely preserved.
[0114] Figure 7 The blood absorption was obtained by using the SD rat liver trauma model and the rat tail amputation model ( Figure 7 A) and hemostasis time ( Figure 7 B) Four groups of data. It can be seen that compared with single OBC, the hemostasis time of other compound groups is shorter and the blood loss is less, especially after compounding iron ions, the hemostasis time is the shortest and the blood absorption is the smallest. In the liver hemostasis model, OBC, OBC / TA, OBC / Ca 2+ / TA、OBC / Fe 3+ / TA and OBC / Mg 2+ The blood absorption of OBC, OBC / TA and OBC / Ca were 222 mg, 126 mg, 52 mg, 26 mg and 57 mg, respectively, and the hemostasis time was 271 s, 201 s, 158 s, 129 s and 164 s, respectively. 2+ / TA、OBC / Fe 3+ / TA and OBC / Mg 2+ The blood absorption of / TA was 249mg, 133mg, 61mg, 36mg and 76mg, and the hemostasis time was 291s, 231s, 164s, 95s and 198s, respectively. This may be because compared with the hemostasis of a single material, the composite material can exert multiple synergistic mechanisms to quickly stop bleeding.
[0115] Figure 8 HE and Masson staining of subcutaneous embedding materials of SD rats. It can be seen that after one week, the OBC control group had obvious inflammatory response, and OBC / TA and OBC / Ca 2+ / TA and OBC / Mg 2+ / TA group had no obvious inflammation, while OBC / Fe 3+ / TA had almost no obvious inflammatory reaction. After four weeks, the inflammatory reaction in each group had disappeared, and most of the materials were degraded, and the tissue cells replaced the materials or merged with the materials. 3+ / TA tissue heals best, and connective tissue has grown in the gaps between the materials. This is because tannic acid can effectively inhibit inflammation in the early stages. Trivalent iron ions are not only one of the trace elements required by cells, but also can slowly release TA chelates from the material. By continuously releasing TA and Fe 3 +, promoting cell proliferation and migration, may accelerate the wound healing process and benefit tissue healing.
[0116] Fig. 9 is the complex amount of catechins and anthocyanins in the OBC material with or without iron ions. It can be seen that Fe 3+ It can also increase the composite amount of the two by nearly 2 times, thereby improving the antibacterial, hemostatic and antioxidant capabilities of the material.
[0117] Fig.10 The results show that the materials prepared in Examples 6-9 have a stronger hemostatic ability in vitro. The materials containing catechins and anthocyanins have a stronger hemostatic ability than pure OBC sponges. Among them, the oxidized bacterial cellulose / iron ions / anthocyanins and oxidized bacterial cellulose / iron ions / catechins composite materials have a stronger hemostatic effect than oxidized bacterial cellulose / anthocyanins and oxidized bacterial cellulose / catechins composite sponges.
[0118] The present invention skillfully combines the two materials without destroying the original structure, and the obtained composite material has broad-spectrum antibacterial properties, excellent blood compatibility and excellent hemostatic properties. It can play an anti-inflammatory and antioxidant role, promote tissue healing, and accelerate the absorption of the material in the body. It has great potential as a hemostatic material in clinical practice.
Claims
1. An absorbable hemostatic composite material for anti-inflammatory and healing of acute bleeding sites, characterized in that: Oxidized bacterial cellulose is prepared by using bacterial cellulose as a substrate, and then self-assembled by electrostatic adsorption with metal ions, and complexed and loaded with natural anti-inflammatory compounds containing phenolic hydroxyl groups; the metal ions are iron ions.
2. The absorbable hemostatic composite material according to claim 1, characterized in that: The oxidized bacterial cellulose is obtained by taking bacterial cellulose as a substrate, oxidizing it and rinsing it with deionized water until it becomes neutral.
3. The absorbable hemostatic composite material according to claim 1, characterized in that: The natural anti-inflammatory compound containing phenolic hydroxyl group is one or more of tannic acid, catechin and anthocyanin.
4. A method for preparing the absorbable hemostatic composite material for anti-inflammatory and healing of acute bleeding sites as claimed in claim 1, comprising the following steps: (1) Using bacterial cellulose as a substrate, preparing an oxidized bacterial cellulose suspension; (2) dripping a metal ion solution into an oxidized bacterial cellulose suspension for mixed adsorption, then dripping an aqueous solution of a natural anti-inflammatory compound containing phenolic hydroxyl groups into the oxidized bacterial cellulose suspension drop by drop for metal ion complexation reaction, followed by centrifugal rinsing, redispersing evenly, and freeze-drying to obtain an absorbable hemostatic composite material.
5. The preparation method according to claim 4, characterized in that: The preparation steps of the oxidized bacterial cellulose suspension in step (1) are as follows: the bacterial cellulose membrane is dispersed by a homogenizer, oxidized by a TEMPO / NaBr / NaClO mixed oxidation system at room temperature, and obtained after centrifugal washing and dialyzation.
6. The preparation method according to claim 4, characterized in that: The aqueous solution of natural anti-inflammatory compounds containing phenolic hydroxyl groups in step (2) is one or more of a tannic acid aqueous solution, a catechin aqueous solution, and anthocyanin aqueous solution with a concentration of 1-5 wt%.
7. The preparation method according to claim 4, characterized in that: The metal ion solution in step (2) is an aqueous solution of ferric chloride with a concentration of 0.1-1 mg / mL.
8. The preparation method according to claim 4, characterized in that: The mass ratio of the natural anti-inflammatory compound containing phenolic hydroxyl groups to the oxidized bacterial cellulose in the step (2) is 1:1-1:
5.
9. The preparation method according to claim 4, characterized in that: In the step (2), the adsorption time is 0.5-5 hours; and the complexation reaction time is 1-60 minutes.
Citation Information
Patent Citations
Method for preparing modified regenerated cellulose / alginate hemostatic composite material
CN104013991A
Preparation method of multi-wall carbon nano tube / chitosan / oxidized regenerated cellulose composite hemostatic material
CN105056284A
Preparation method of oxidized nano-cellulose / collagen composite sponge
CN105079886A
Novel degradable hemostatic material and preparing method thereof
CN110339391A
Local acute bleeding-stopping absorbable material and preparation method thereof
CN110141677A